Effect of liming and fertilizer application in hemic and sapric of tropical peat: phosphorus mineralization, infra-red spectroscopy and microscopy - Abdul Reeza, Ameera; Hussin, Aminuddin; Mohd Hanif, Ahmad Husni; Md. Sukari, Mohd Aspollah (Science Publications, 2014)
This study was conducted to investigate the changes in nutrient level P as well as in the structural and functional groups upon the decomposition of Hemic and Sapric peat material due to application of lime and fertilizers. The peat materials were left to decompose for 8 weeks under laboratory incubation and samples were taken for the determination of extractable P at 1 week interval. At 8 weeks, samples were sent for FTIR and SEM analysis. Although both types of peat material exhibit similar patterns in the mineralization of phosphorus, however, the amount of extractable phosphorus between Hemic and Sapric during the decomposition process differed. Addition of fertilizer (T3) resulted in a significantly large increase in extractable P compared to T1 and T2 but the effect was temporal as the extractable P declined throughout the incubation period. Sapric material displayed more absorption bands from the FTIR spectral analysis compared to Hemic although there were few similarities between the bands produced. Application of fertilizer in T3 caused the peaks that were similar with other treatments became weaker and different functional groups were shown at lower frequencies. Images from SEM showed that addition of lime and fertilizers caused the collapsing and degradation of the plant cell structures in the organic materials of the peat justifying the process of decomposition had occurred. Hemic and Sapric peat material showed some similarities as well as differences in extractable P, plant cell structures and spectral bands upon the application of lime and fertilizers.